From carrot to clinic: an overview of the retinoic acid signaling pathway - Theodosiou, Maria; Laudet, Vincent; Schubert, Michael (Cellular and molecular life sciences : CMLS, 2010)
Vitamin A is essential for the formation and maintenance of many body tissues. It is also important for embryonic growth and development and can act as a teratogen at critical periods of development. Retinoic acid (RA) is the biologically active form of vitamin A and its signaling is mediated by the RA and retinoid X receptors. In addition to its role as an important molecule during development, RA has also been implicated in clinical applications, both as a potential anti-tumor agent as well as for the treatment of skin diseases. This review presents an overview of how dietary retinoids are converted to RA, hence presenting the major players in RA metabolism and signaling, and highlights examples of treatment applications of retinoids. Moreover, we discuss the origin and diversification of the retinoid pathway, which are important factors for understanding the evolution of ligand-specificity among retinoid receptors.